First to respond, last to leave: Communities' roles and resilience across the '4Rs'. (December 2015) - Vallance, Suzanne; Carlton, Sally
Abstract: Shortly after the second major earthquake in Canterbury, New Zealand in 2011, an inventory of the activities and initiatives of community groups and NGOs was conducted. Another two inventories were undertaken in 2012 and 2013. Analysis of these three inventories reveals some significant changes in both the types of activities being undertaken and the 'communities' responsible for them. The inventories document a rapid increase in the number of community groups and non-governmental organisations playing a role in recovery. An important finding is that most of those active almost 4 years after the first earthquake were actually in operation before the earthquakes and have since layered recovery work over their core business. In building resilience to all hazards, we therefore argue for better recognition of the potential roles that different communities play, not only in recovery, but across all phases of disaster risk reduction. These roles range from administering first aid through to co-producing knowledge underpinning risk management strategies and actions. We argue that different types of communities have the potential to weave disaster readiness, response and recovery, and risk reduction into their core business, and therefore represent a valuable – though often underestimated and poorly understood – resource.